Eksplorasi Mineral Ekonomi dan Genesisnya: Mineral Bijih Cu-Au Busur Sunda-Banda - Aly Rasyid (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
This study is based on initial findings indicating Cu-Au minerals in altered igneous rocks in the prospect zone around Sumbawa. The main problem studied is how outcrop, petrology, mineralogy, hydrothermal alteration, and geochemistry data can be used to reconstruct the relationship between rock petrogenesis and ore mineral formation. The approach used is a synthesis of research data with nearby regional analogs from the Sumbawa segment and the eastern Sunda arc, so that interpretation does not depend on a single mine site, but on the geological, petrologic, and metallogenic patterns that have been documented in the area. The data evaluated include outcrop indications of porphyritic igneous rocks, quartz-sulfide veins, potassic to propylitic alteration, petrography-XRD-SWIR-based identification of alteration minerals, chemical characteristics of intermediate-felsic rocks, and geochemical patterns of Cu, Au, Mo, Ag, As, Pb, Zn, and other trace elements. The synthesis results show that Cu-Au indications are most consistently explained as part of a porphyry-type magmatic-hydrothermal system, which developed in the Sunda-Banda subduction arc environment. The hydrous, relatively oxidized arc magma, which evolved towards tonalite-quartz diorite, became the source of heat, fluids, and metals. The release of magmatic-hydrothermal fluids then produced quartz-sulfide stockworks, chalcopyrite-bornite-pyrite mineralization, as well as potassic, phyllic/chlorite-sericite, argillic, and propylitic alteration zones. The integration of these data allows the development of a more systematic genesis model while providing the basis for exploration vectorization from the distal alteration zone to the mineralization center.